2022
DOI: 10.1111/ejh.13834
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis for inpatient with advanced cancer receiving palliative care: A retrospective study

Abstract: Objectives The benefits and risks of thromboprophylaxis usage in patients with advanced cancer at the end of their lives remain unknown, especially with the lack of randomized studies. This study aimed to describe the clinical use of thromboprophylaxis in those patients under palliative care. Methods A retrospective cohort study. It was performed on patients admitted to the Palliative Care Center. Results A total of 719 patients were enrolled in the study. The mean age was 62.97 (13.65) years. Venous thromboem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…The incidence of clinically suspected fatal VTE was 6.5%, and statistically it was higher in the group of patients taking antithrombotic prophylaxis than in the group of people who were not taking it. 28 The authors of another small prospective study on a group of 127 patients whose life expectancy was shorter than 6 months found that primary antithrombotic prophylaxis may not be included or even safely discontinued in patients previously taking it who were admitted to a palliative care unit. Of all participating patients, 41 (32.3%) were taking prophylaxis on admission.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of clinically suspected fatal VTE was 6.5%, and statistically it was higher in the group of patients taking antithrombotic prophylaxis than in the group of people who were not taking it. 28 The authors of another small prospective study on a group of 127 patients whose life expectancy was shorter than 6 months found that primary antithrombotic prophylaxis may not be included or even safely discontinued in patients previously taking it who were admitted to a palliative care unit. Of all participating patients, 41 (32.3%) were taking prophylaxis on admission.…”
Section: Symptomsmentioning
confidence: 99%
“…Al.-Ansari et al 28 719 patients Cancer patients with a short expected survival time will not benefit from the use of prophylaxis, because it does not reduce the risk of fatal VTE in patients in the terminal phase of cancer. 9…”
Section: Study Reference Study Population Findingsmentioning
confidence: 99%